1998
DOI: 10.1099/00221287-144-5-1299
|View full text |Cite
|
Sign up to set email alerts
|

A chitin-binding domain in a marine bacterial chitinase and other microbial chitinases: implications for the ecology and evolution of 1,4-β-glycanases

Abstract: To examine the ecology and evolution of microbial chitinases, especially the chitin-binding domain, one of the chitinase genes (&A) from the marine bacterium Vibrio harveyi was analysed. The deduced amino acid sequence of ChiA is not very similar overall to other proteins, except for two regions, the putative catalytic and chitin-binding domains. Among all bacterial chitinases sequenced to date, there is no relationship between percentage similarity of catalytic domains and chitin-binding domains in pairwise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 44 publications
3
75
0
4
Order By: Relevance
“…Different chitin-binding domains enable attachment to various types of chitin (Svitil and Kirchman, 1998). Svitil and Kirchman (1998) found that endochitinase activity from the V. harveyi chiA gene increased upon removal of the chitin-binding domain, as this changed the enzyme's accessibility to glycosidic bonds within a chitin strand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different chitin-binding domains enable attachment to various types of chitin (Svitil and Kirchman, 1998). Svitil and Kirchman (1998) found that endochitinase activity from the V. harveyi chiA gene increased upon removal of the chitin-binding domain, as this changed the enzyme's accessibility to glycosidic bonds within a chitin strand.…”
Section: Discussionmentioning
confidence: 99%
“…Different chitin-binding domains enable attachment to various types of chitin (Svitil and Kirchman, 1998). Svitil and Kirchman (1998) found that endochitinase activity from the V. harveyi chiA gene increased upon removal of the chitin-binding domain, as this changed the enzyme's accessibility to glycosidic bonds within a chitin strand. In B. circulans, when the chiA1 chitin-binding domain was cloned separately from the gene in which it is located and expressed, the ChiA1 domain protein maintained its structure and function (Ikegami et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBM2 domains are found in bacterial family 18 chitinases, while CBM5/12s are frequently found in both family 18 and 19 chitinases, as well as in some CBPs (CAZy, 2013;Punta et al, 2012;Karlsson & Stenlid, 2009). Functional studies on chitin-binding properties of CBM2 and CBM5/12 have mainly focused on the role of the latter, but both domains have been shown to enhance substrate affinity and increase catalytic efficiency of chitinases (Watanabe et al, 1994;Hashimoto et al, 2000;Svitil & Kirchman, 1998;Nakamura et al, 2008), in a manner likely dependent on certain conserved surface-exposed aromatic residues (Morimoto et al, 1997).…”
Section: Classification Of Chitin-binding Modules Of Chitinases and Cbpsmentioning
confidence: 99%
“…Based on sequence analyses the GH family 18 enzymes have been separated into different groups (Karlsson & Stenlid, 2009;Svitil & Kirchman, 1998;Watanabe et al, 1993). This classification illuminates the phylogenetic relationships between catalytic domains, but has so far not offered insights regarding distinct roles of biological significance.…”
Section: Classification Of Hydrolytic Domains Of Chitinasesmentioning
confidence: 99%